Substituent Effect on Carbonyl and Carboxylate Stretching Frequencies of Phenacyl Benzoates - Ravi, S.; Palani, M.; Krishna Pillay, M. (Asian Journal of Chemistry, 2010)
In the present communication, the substituent effects on carbonyl and carboxylate stretching frequencies of phenacyl benzoates have been studied.